Simplification Complex Sentences in Indonesia Language using Rule-Based Reasoning - Rifka Widyastuti; M Fachrurrozi; Novi Yusliani (ICON-CSE, 2014)
Complex sentence consist of two or more single sentence and one or more conjunctions. Complex sentences have many meaning, so that is quite difficult to be simplified because the results of simplification complex sentence does not match the original sentence. To solve this problem, this research using Rule-Based Reasoning method and Surface Expression Rules. Because Rule-Based Reasoning method can be adapted to the rules of surface expression that can look for patterns of complex sentences, so thus simplifying precise and accurate results. The results of researchis the Rule-Based Reasoning methods used in accordance with the accuracy of 93.8% and an assessment of questionnaires obtained values 76-100